Guptajī kī kalā : kavi Śrī Maithilīśaraṇa Gupta kī racanāoṃ kā eka ālocanātmaka adhyayana - Satyendra, 1907- (SAMP early 20th-century Indian books project, 1942)
Study of the style of Maithili Sarana Gupta, 1886-1964, Hindi poet.